Wastewater use in agriculture - Qadir, Manzoor; Drechsel, Pay; Raschid-Sally, Liqa (Informa UK Limited, 2013)
Under conditions of increasing water scarcity and water quality deterioration, farmers have often little alternative to the use of raw or diluted wastewater to irrigate a range of crops. Aside from the agronomic benefits of resource recovery, the practice carries risks for farmers, public health, and the environment. A range of criteria have to be considered if such water sources are used: 1) crop selection and diversification to reduce possible health risks, accounting for market value and tolerance against ambient stresses; 2) irrigation water management covering water access, on-farm treatment, type of irrigation, application rates, and scheduling; and 3) soil-health-based considerations such as soil characteristics, soil preparation practices, and application of fertilizers and amendments. The awareness of farmers about the best management practices is essential for safe and sustainable wastewater irrigation.